IOT BASED HOME SAFETY GAS LEAKAGE DETECTION AND AUTOMATIC BOOKING SYSTEM - Christal Mary .S, Suma; Leela.R, Josphine; .R, Vedhapriyavadhana; Rajathi.G, Ignisha (International Journal of Psychosocial Rehabilitation, 2024)
Gas spillages causes a significant issue in family unit, in this way the proposed gas spillage identification and checking framework is created There are numerous strategies accessible for booking a Gas Refill, techniques incorporate web based booking, telephonic booking and so on. It will be difficult situation for the individual who uses LPG gas for cooking reliably. The aim of this paper is to introduce another framework consequently books a cylinder at the point when the gas is going to discharge is bysending a notice to the gas office using Wifi using Internet of Things approach In addition to that sensor is utilized to identify gas spillage at home. On the off chance that the gas spillage is sensed, the gadget continues ahead with ringer caution and showing ready message in LCD show at the same time switch on the fumes fan and turn over the DC engine, is made to kill the gas regulator, PIR sensor additionally put in the home to inform about the human nearness. In the event that no individual, naturally power off simultaneously the notice will be sent to client through versatile by notice calls and SMS. Wifi is one of the most utilized systems over the world. Henceforth, load cell has been utilized to screen the heaviness of the LPG gas consistently. The values are next taken care of to the Arduino microcontroller. By utilization of GSM Module, the data is sent to client by SMS and furthermore programmed booking is finished by dialing the enlisted gas booking number. Consequently, answer warning will be sent to the client about the booking status. This, work this causes the general public to explicitly demonstrate gas spillage and furthermore helps the two clients and the office to get the gas booking made consequently utilizing the IOT procedure